Autograft Anatomic, Double-Bundle Posterior Cruciate Ligament Reconstruction - Ponzo, Nelson (Arthrosc Tech, 2018)
It is well known that the posterior cruciate ligament (PCL) is the main stabilizer to posterior tibial translation in the knee. Anatomic double-bundle reconstruction has recently been proposed to best restore posterior and rotational tibial instability, especially compared with a single-bundle PCL reconstruction (PCLR). Most publications in the peer-reviewed literature on double-bundle PCLR have used allografts. However, in many countries, allografts are not available. This Technical Note describes an all-autograft arthroscopic technique for PCLR using the quadriceps and semitendinosus tendons.